Enhanced electrode kinetics and electrochemical properties of low-cost NaFe2PO4(SO4)2 via Ca2+ doping as cathode material for sodium-ion batteries. (10th July 2021) - Li, Shao-Fang; Gu, Zhen-Yi; Guo, Jin-Zhi; Hou, Xian-Kun; Yang, Xu; Zhao, Bo; Wu, Xing-Long
Highlights: The developed NaFe2 PO4 (SO4 )2 materials are low-cost cathode candidate for sodium-ion batteries. Its electrochemical properties and electrode kinetics have been significantly improved via Ca 2+ doping. The introduction of Ca 2+ broadens the diffusion channels of Na + . GITT and CV tests show that its Na + diffusivity values are around at 10 −12 cm 2 s −1 . Abstract: In recent years, sodium-ion batteries (SIBs) have been considered as one of the most promising alternatives to lithium-ion batteries (LIBs). Here, a new Na-super-ionic conductor (NASICON) cathode material NaFe2 PO4 (SO4 )2 is successfully prepared through solid state method for SIBs. While the poor electronic conductivity of iron-based materials results in its poor rate and cycle performance. Then the electrochemical is effectively promoting via Ca 2+ doping. Na0.84 Ca0.08 Fe2 PO4 (SO4 )2 have achieved considerable electrochemical properties. The first discharge specific capacity is 121.6 mA h g −1 at 25 mA g −1 with the voltage platform (∼3.1 V) corresponding to Fe 2+/3+ . After 100 cycles, the capacity retention is 55.1 %. The excellent electrochemical performance is caused by some Na + is substituted by Ca 2+ and leading to the fast sodium kinetics, which is well proved by the powder X-ray diffraction pattern and well corresponding to the galvanostatic intermittent titration technique and cyclic voltammetry testing result (the diffusivity values are around at 10 −12 cm 2 s −1 ).